Disentangling the bond-CDS nexus: a stress test model of the CDS market - Guillaume Vuillemey; Tuomas A. Peltonen (European Central Bank (ECB), 2013)
This paper presents a stress test model for the CDS market, with a focus on the interplay between banks' bond and CDS holdings. The model enables the analysis of credit risk transfer mechanisms, includes features of market and liquidity risk, and allows for contagious propagation of counterparty failures. As an illustration, we calibrate the model using sovereign bond and CDS data for 65 major European banks. The model simulation shows that, in case of a sovereign credit event, banks' losses due to direct and correlated bond exposures are significantly higher than losses due to CDS exposures. The main risk for CDS sellers is found to be sudden increases in collateral requirements on multiple correlated CDS exposures. Close-out netting considerably reduces the extent to which contagion may occur.
Keywords: G21; H63; G15; 330; collateral; Contagion; credit default swap; credit event; liquidity risk; market risk; stress test